Efeito antinociceptivo, gastrointestinal e na atividade locomotora espontânea da administração intravenosa e metadona em equinos - Oliveira, Flávia Augusta de [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Opioids are the most potent substances used for pain relief. However, these drugs are not widely used in horses, due to substantial sympathetic stimulation, excitement of the central nervous system and decreased of the gastrointestinal motility observed when opioids are administered intravenously. The effects of methadone on antinociception, spontaneous locomotor activity and gastrointestinal motility were investigates. Six adult horses were used in a randomized crossover design. Each animal was subjected to three treatments: saline (control), methadone (0.2 mg / kg - MET0.2) and methadone (0.5 mg / kg - MET0.5) intravenously (IV), within 1 week between each treatment. The antinociceptive effect was evaluated by the hoof- withdrawal reflex latency (HWRL) after painful stimulation with a heat lamp and voltage for the withdrawal reflex of the limb (VRRM) after electrical stimulation (phase 1). Spontaneous locomotor activity (SLA ) was investigated in a behavior box by use of infrared photoelectric sensors (phase 2) and gastrointestinal motility by abdominal auscultation (phase 3). Parametric variables were analyzed by ANOVA followed by Dunnett or Tukey test. For SLA and abdominal auscultation was fitted the generalized linear models with Poisson error and log link function for repeated data. Differences were considered significant when P <0.05.No electrical noxious stimulation test was performed with the dose of 0.5 mg/kg methadone IV. The HWRL did not increase in animals treated with MET0,2. However, after administration of 0.5 mg/kg of methadone IV, HWRL increased significantly at 15 and 30 minutes compared to baseline and control groups and MET0,2, rising from 3,21 seconds (average) to 8.61 and 9.11 seconds respectively (P <0.05). VRRM increased significantly from baseline at all... (Complete abstract click electronic access below)
Keywords: Analgesia; Sistema gastrointestinal - Motilidade; Antinociception